2022
DOI: 10.3399/bjgpo.2021.0227
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity promotion by GPs: a cross-sectional survey in England

Abstract: BackgroundPhysical activity (PA) contributes to the prevention and management of many health conditions. Primary care practitioners have an important role to play in supporting people to be physically active.AimThe study had three aims; 1) to explore general practitioners’ (GPs) awareness, and knowledge of the PA guidelines, 2) to assess their confidence in promoting PA, and 3) to explore factors that influence PA promotion amongst GPs.Design & settingCross-sectional survey, secondary analysis.MethodUK-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Improving inactivity levels in society is a complex and multifactorial issue, demonstrated well by the fact that limited solutions have been developed to combat the rise in physical inactivity despite extensive evidence of the benefits of being active for health and quality of life. The findings of this study are in line with previous papers highlighting the lack of knowledge and confidence of HCPs in giving PA to patients [10,[20][21][22]. Indeed, 10% of junior doctors felt they had been adequately trained in PA [23].…”
Section: Improving Knowledge Confidence and The Priority Given To Pro...supporting
confidence: 90%
See 3 more Smart Citations
“…Improving inactivity levels in society is a complex and multifactorial issue, demonstrated well by the fact that limited solutions have been developed to combat the rise in physical inactivity despite extensive evidence of the benefits of being active for health and quality of life. The findings of this study are in line with previous papers highlighting the lack of knowledge and confidence of HCPs in giving PA to patients [10,[20][21][22]. Indeed, 10% of junior doctors felt they had been adequately trained in PA [23].…”
Section: Improving Knowledge Confidence and The Priority Given To Pro...supporting
confidence: 90%
“…A similar finding of lack of priority to PA advice during consultations was found amongst physiotherapists [22]. Interestingly, one study found that 98.9% of GPs believe that PA is important for health [10]. Therefore, while the benefits are well acknowledged by doctors, it continues to not be thought of as a priority during consultations.…”
Section: Improving Knowledge Confidence and The Priority Given To Pro...mentioning
confidence: 58%
See 2 more Smart Citations
“…But further to this, recent research suggests that these are the two most widely recognised tools for helping people into the world of running. In a 2021 survey exploring general practitioners' awareness of physical activity promotion, it was found that “‘Couch to 5 K’ and the ‘parkrun practice’ initiative were the most widely known and used” physical activity promotion tools ( 12 ). When combined, parkrun and Couch to 5 K have a significant market share when it comes to beginner running initiatives and the impact and influence that they have had is reflected in their representation in popular fiction.…”
Section: The 5 K Movementmentioning
confidence: 99%